Sarcopenia modelling by portal vein ligation inducing hyperammonemia in rats - Maria Nadinskaia; Kseniya Gulyaeva; Aleksandr Sukhinin; Alla Sedova; Polina Boykova; Ilya Izmailov; Ksenia Pokidova; Egor Kuzmin; Artem Venediktov; Igor Meglinski; Gennadii Piavchenko (PLoS ONE, 2025)
Sarcopenia is a progressive muscle wasting condition often associated with hyperammonemia. However, no approved animal models of sarcopenia with hyperammonemia were reported. This study aimed to provide a surgical modelling of sarcopenia with hyperammonemia. Male Wistar rats were assigned by the method of random numbers ( n = 6 per group) into experimental group with ligation of portal and pyloric veins or control group with sham surgery. Blood ammonia levels were measured directly after the surgery (20 min), after 1 h to observe acute damage in functioning shunts, and at the final endpoint (30 days). Rats were sacrificed with histological study of the liver, spleen, cerebral cortex, and skeletal muscles. Experimental rats revealed hyperammonemia at 30 days compared to controls, 70 µmol/L versus 38 µmol/L, p <0.05. No significant changes were observed in liver morphology between the groups, approving hyperammonemia without liver damage. Splenomegaly and Gamna-Gandy bodies in the spleen of experimental rats indirectly evidenced functionable portosystemic shunting after the ligation. Cerebral cortex showed a significant decrease in neurons of experimental animals, 7.6 ± 2.5 NeuN + cells vs 13 ± 2 in controls, p <0.05. Skeletal muscles revealed a significant difference of muscle fiber diameter between the groups, 20.2 ± 2.1 µm in the experimental group vs 30.7 ± 4.3 µm in controls, at p < 0.001. A model of sarcopenia with hyperammonemia was established with concomitant changes in cerebral histology revealed. This model may be a valuable tool for studies of sarcopenia and related therapeutic options.